Validation of the Malayalam version of the parental stressor scale: Pediatric intensive care unit - Janani Sethuraman; Chitra Venkateswaran (Wolters Kluwer Medknow Publications, 2021)
Background: For any research, it is important to ensure that an establish instrument conforms to the culture of the population in focus. The objectives of this study include translation of the Parental Stressor Scale: Pediatric Intensive Care Unit (PSS: PICU) questionnaire into Malayalam and the analysis of its psychometric properties. Subjects and Methods: This was a cross-sectional study of 201 parents of children admitted to the PICU. The PSS: PICU questionnaire was first translated into Malayalam language using the standard "Forward-Backward" procedure. Following consent, parents completed the demographic sheet and the Malayalam version of PSS: PICU scale within 30 min. Results: Analysis showed good psychometric properties for the Malayalam PSS: PICU questionnaire when compared to the original English version. The principal component factor analysis with Varimax rotation was used to assess the validity and was found to favor the conceptual dimensions of the original English questionnaire. The Cronbach's alpha coefficient used to assess reliability was 0.865 for the entire scale reflecting good internal consistency. Conclusion: The PSS: PICU questionnaire was translated to Malayalam and the psychometric properties of the Malayalam version were found to be adequate, albeit requires further exploration before extensive use.